Validity and Reliability of the 3-E Tool for Evaluating the Curriculum Support Intervention in Uganda - Milton Mutto; Mukasa Immaculate; Avasi Victor; Kalabi Charles; Kamwesigye Charles; Duku Tom (Institute of Advanced Engineering and Science, 2015)
This study determined psychometric properties of 3-ET, an instrument specifically designed to track the effects of a curriculum support intervention created to enhance the delivery of the national curriculum in a war zone in Uganda. The instrument was developed through brain storm and expert review before being committed to structural and reliability testing using Exploratory Factor analysis (EFA). The 88 variables of 3-ET were reduced to 73; five distinct sub-scales emerged. Sub-scale 1, measured core education support functions and services. Sub-scale 2, assessed aesthetics/efficiency. Sub-scale 3, focused on barriers to stakeholder participation. Sub-scale 4 measured peacefulness and gender sensitivity of learning environments. Sub-scale 5 assessed pupil participation. 3-ET has acceptable structural validity and internal consistence reliability. It can be used to test effectiveness of the REPLICA intervention. Its applicability in other conflict and non-conflict contexts needs review.